Attentional Blink in Pilots and Its Relationship With Flight Performance - Li, Fengzhan; Liu, Quanhui; Lu, Huijie; Zhu, Xia (Frontiers in Psychology, 2020)
Objective: In flight, military pilots need to monitor the changes of the external environment, and pay attention to the situation of aircraft at the same time. Attentional blink (AB) reflects the attentional blindness in time course. Therefore, the present study investigates the AB effect of military pilots and its relationship with flight performance. Methods: 30 male military pilots (44.23 ± 4.07 years old) and 29 normal male participants (44.07 ± 2.93 years old) were tested by the classic rapid serial visual presentation paradigm. The accuracy of detecting the second target stimulus (T2) on the basis of response to the first target stimulus (T1) was calculated to measure the attentional blink effect. The flight performance of these military pilots were also collected. Results: The accuracy of both groups in detecting T2 at the positions of 180ms, 270ms, 360ms and 450ms were significantly lower than that of T1. The military pilots’ detection accuracy of T2 at the positions of 180ms (t = 3.68, p＜0.001) and 270ms (t = 3.66, p＜0.001) were significantly higher than that of normal participants, and the mean accuracy of T2 (AB effect) at the positions of 180ms, 270ms, 360ms and 450ms was also significantly higher than that of normal participants (t = 3.35, p＜0.001). There was a significant correlation between the AB effect and the lowest score of flight performance for the military pilots (r = 0.52, p = 0.004), and the regression effect was significant (β = 0.514, p = 0.004, R 2 = 0.31). Conclusions: Both groups experienced the AB effect, but military pilots’ performance in AB effect is better than that of the ordinary people. The AB effect of military pilots can predict the lowest score of flight performance. These findings may have implications for the grounding and selection of Chinese military pilots.